Total Syntheses of (+)‐Sarcophytin, (+)‐Chatancin, (−)‐3‐Oxochatancin, and (−)‐Pavidolide B: A Divergent Approach. Issue 15 (12th March 2019) - He, Chuan; Xuan, Jun; Rao, Peirong; Xie, Pei‐Pei; Hong, Xin; Lin, Xufeng; Ding, Hanfeng
Abstract: A concise and divergent approach for the total syntheses of four cembrane diterpenoids, namely (+)‐sarcophytin, (+)‐chatancin, (−)‐3‐oxochatancin, and (−)‐pavidolide B, has been developed, and it also led to the structural revision of (−)‐isosarcophytin. The key steps of the strategy feature a double Mukaiyama Michael addition/elimination, a Helquist annulation, two substrate‐controlled facial‐selective hydrations, and a pinacol rearrangement. The described syntheses not only achieved these natural products in an efficient manner, but also provided insight into the biosynthetic relationship between the two different skeletons. Abstract : Efficient access : A concise and divergent approach for the total syntheses of four cembranoids, namely (+)‐sarcophytin, (+)‐chatancin, (−)‐3‐oxochatancin, and (−)‐pavidolide B, was developed. The key features of the efficient strategy entail a double Mukaiyama–Michael addition/elimination, a Helquist annulation, two facial‐selective hydrations, and a pinacol rearrangement.